2019
DOI: 10.1177/0194599819874842
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis in Pediatric Primary Ciliary Dyskinesia: Impact of Disease

Abstract: Objectives Primary ciliary dyskinesia (PCD) is a genetic disorder characterized by abnormal respiratory cilia ultrastructure and/or function causing defective mucociliary clearance. We investigated the extent and severity of rhinosinusitis in a large cohort of children with PCD and explored associations among risk factors, including genotype and sinus disease. Study Design Retrospective chart review. Setting Tertiary academic children’s hospital. Subjects and Methods A review was conducted with a patient regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…The exact prevalence of PCRS in patients with underlying conditions such as CF, PCD, or immunodeficiency is unknown but may be higher than in healthy children. Depending on the diagnostic criteria used for PCRS, some studies estimate the incidence of PCRS in children with CF to be 11% to 38%, 38,2321 for children with PCD to be as high as 40%, 39 and for children with CVID to be as high as 36% 40 …”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
See 3 more Smart Citations
“…The exact prevalence of PCRS in patients with underlying conditions such as CF, PCD, or immunodeficiency is unknown but may be higher than in healthy children. Depending on the diagnostic criteria used for PCRS, some studies estimate the incidence of PCRS in children with CF to be 11% to 38%, 38,2321 for children with PCD to be as high as 40%, 39 and for children with CVID to be as high as 36% 40 …”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
“…Rhinosinusitis is common in patients with PCD, 39 though overall PCD is a rare cause of PCRS based on its low prevalence. A diagnosis of PCD should be considered in cases of refractory PCRS, particularly with concomitant chronic otitis media.…”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
See 2 more Smart Citations
“…41 A recent review noted that sinusitis is relatively common in primary ciliary dyskinesia patients, although most did not require ESS, develop complications, or require hospitalization. 42 A systematic review of pediatric patients with this condition found that studies detailing surgical outcomes and validated measure use were sparse and suggested the formulation of a multicenter database to better study chronic sinusitis in this population. 43 A limitation of this study includes the exclusion of non-English abstracts, which could potentially overrepresent the influence of English literature on the topic.…”
Section: Discussionmentioning
confidence: 99%